Ignition of bio-water-coal fuel drops; Energy; Vol. 203 - Syrodoy S. V. Semen Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Gutareva N. Yu. Nadezhda Yurievna; Purin M. V. Mikhail Vladimirovich (2020, 2020)
Title screen